DAMPAK MEDIA SOSIAL TERHADAP POLA INTERAKSI SOSIAL BUDAYA SISWA DI SEKOLAH SDN 01 DESA TERUSAN MENANG SP PADANG KABUPATEN OGAN KOMERING ILIR - Fatimatuzzahra, Fatimatuzzahra; Juliana, Siti Arbaina; Riyani, Roja (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2024)
Social media is a social interaction between individuals in sharing and exchanging information. Social media can include various ideas, opinions, notions and content in virtual communities and is able to present and translate new ways of communicating with technology that is completely different from traditional media (Watson, 2009). The development of the increasingly innovative world of technology in the global era has had a direct impact on society, especially the younger generation. The term social media is composed of two words, namely "media" and "social". "Media" is defined as a means of communication. Meanwhile, the word "social" is defined as the social reality that every individual carries out actions that contribute to society. Personality development Innate and environmental factors influence each person. According to developmental psychologists, every person has innate potential revealed after birth, including abilities related to personality or virtue. According to Confucius, humans basically have the capacity to love virtue, but if this potential is not maintained through education and socialization after humans are born, humans can become animals, or worse, animals.